ANALISIS PERBEDAAN PENDAPATAN PETANI KARET BOKAR (BAHAN OLAHAN KARET RAKYAT) BERDASARKAN MUTU DI KECAMATAN MUARA TABIR KABUPATEN TEBO - Susridar, Susridar; Wibisonya, Irawan (Institute of Computer Science (IOCS), 2024)
The plantation sector in Jambi Province is a mainstay sub-sector in economic development, especially the rubber commodity. Rubber is a plant that has become a culture for the people of Jambi Province as a basic livelihood. Therefore, this plant has quite an important history for plantation farmers in Jambi Province. Besides that, the contribution of rubber plants to the GRDP of Jambi Province is quite good compared to other commodities. Then for Muara Tabir District, the livelihood of the population is farming with rubber plantations. The area of ??rubber plantations in Muara Tabir District is 6,506 ha, with a production of 1,093 tons and a productivity of 0.26 ha with a total of 10,978 families of farmers spread across eight villages. People's plantations generally produce rubber in the form of processed rubber material (bokar). The processed rubber material produced by farmers in Muara Tabir District is in the form of thick slabs with different qualities and sizes, high quality bokar if the thickness is 15 to 25 cm with a Dry Rubber Content (KKK) >- 50%, while bokar has a thickness above 25 cm is said to have low quality plus a Dry Rubber Content (KKK) < 50%. Rubber farmers in Muara Tabir District are generally native residents and transmigrants with an average ownership of rubber plantation land of 2 to 3 ha. Farmers produce rubber in bokar form every day ranging from 18-24 kg with a tapping time of 4-5 days/week. Farmers sell their rubber to local traders (village/district traders) who come to the farmer's house. Farmers sell their rubber 1 to 2 times a week. At the time of observation, the price of bokar in Muara Tabir District was around IDR 7,000/kg - IDR 7,500/kg. The difference in selling prices between farmers and traders is due to traders' assessments based on visuals, namely thickness, dirt, water content or KKK. Determination of bokar quality (dry rubber content) in the field based on observations is a comparison of the farmer's selling price with the indicated price multiplied by 100%. Farmers producing bokar generally focus on weight, even though farmers already understand that good quality bokar will be valued highly. However, the pricing and quality determination are in the hands of the traders.